The Government Auditor Professionalism Determinant - I Gusti Ayu Purnamawati; Ni Ketut Sari Adnyani (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2019)
The aim of this study was to analyze the professionalism of the government auditors in Bali Province. This study is an explanatory research. The samples of this study were 30 respondents. The subjects of this study were all auditors at the Inspectorate of Buleleng Regency, Inspectorate of Denpasar City and Inspectorate of Bali Province. Types of data used was quantitative data, while the data collected by using questionnaires. Data analysis methods used were validity and reliability test, the classical assumption, and the hypothesis were tested using F-test analysis and t-test analysis which were then analyzed using multiple linear regression analysis. All the variables in this study were measured using the likert scale 1-5. The results showed that Motivation, Work Culture, Leadership Style, Gender, and Independence had positive and significant impact on the professionalism of the government auditors. An internal government auditor should improve his professionalism for the efficiency and effectiveness improvement in order to improve public sector performance.